2021
DOI: 10.1111/ijfs.15500
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of dried shiitake, black ear and silver ear mushrooms into sorghum biscuits manipulates the predictive glycaemic response in relation to variations in biscuit physical characteristics

Abstract: Summary The nutritional quality of gluten‐free products is important to the health of individuals with coeliac disease. Mushrooms are good sources of vitamins, dietary fibres and proteins, and are a low‐calorie option that can be used in gluten‐free diets to improve their nutritional value. The effects of incorporating dried mushrooms on the hydration and pasting properties of sorghum flour, as well as the physicochemical characteristics and in vitro glycaemic response of sorghum biscuits were studied. Sorghum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 66 publications
(87 reference statements)
0
15
0
1
Order By: Relevance
“…Часть этих процессов связана как с ковалентной, так и с нековалентной связью между биологически активными ингредиентами и функциональными макромолекулами в пищевых продуктах [15]. Примером этого также являются интенсивные исследования роли пищевых волокон в укреплении здоровья потребителей в возможностях управления усвояемостью углеводов [16][17][18], а также сделан акцент на роли данных соединений в изменении ферментативного поведения микробиоты кишечника [19]. Связывание фенольных соединений с белковыми компонентами может влиять на усвояемость белков и, следовательно, на их доступность с точки зрения клеточного поглощения.…”
Section: результаты исследования и их обсуждениеunclassified
“…Часть этих процессов связана как с ковалентной, так и с нековалентной связью между биологически активными ингредиентами и функциональными макромолекулами в пищевых продуктах [15]. Примером этого также являются интенсивные исследования роли пищевых волокон в укреплении здоровья потребителей в возможностях управления усвояемостью углеводов [16][17][18], а также сделан акцент на роли данных соединений в изменении ферментативного поведения микробиоты кишечника [19]. Связывание фенольных соединений с белковыми компонентами может влиять на усвояемость белков и, следовательно, на их доступность с точки зрения клеточного поглощения.…”
Section: результаты исследования и их обсуждениеunclassified
“…Mushrooms have been studied for their use as meat [19], fat [20], salt [19,20], or flour replacements [14,21,22]. Mushrooms have been used as a food additive in various forms, e.g., fresh or after thermal treatment [19], in the form of powders after drying and grinding [14,23,24], as water extracts [25], or polysaccharide fractions [26]. Preparing mushrooms as a flour substitute involves drying them using various methods [14,27,28] and then grinding the dried mushrooms into powder.…”
Section: Introductionmentioning
confidence: 99%
“…The dehydrated mushroom can be consumed as a low‐cost alternative to meat protein after rehydration and can also be utilized in powder form by incorporating it into different food formulations such as biscuits, nuggets, soup powder, candies, ketchup, noodles, and extruded snacks to enhance the nutritional, physicochemical, rheological, textural, and sensory properties (Brennan et al, 2012; López‐Hortas et al, 2022; Salehi, 2019). Tu et al (2021) prepared gluten‐free biscuits from sorghum flour enriched with mushroom powder and observed an increase in the water absorption capacity and swelling power with a decrease in pasting viscosities as well as diameter, thickness, weight loss, and glycemic response of sorghum biscuits reduced significantly with increasing the addition of mushroom powder. Lu et al (2020) observed that the inclusion of mushroom powder resulted in reduced product expansion, increased water solubility index (WSI), and decreased water absorption index (WAI) with higher levels of antioxidants and phenolic compounds in semolina extruded snack products.…”
Section: Introductionmentioning
confidence: 99%